2009
DOI: 10.2355/isijinternational.49.495
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Circulation Flow Rate in the RH Degasser Using Discrete Phase Particle Modeling

Abstract: Conservation equations for mass and momentum with a two equation k-e model are solved for the continuous phase along with a discrete phase particle modeling (representing gas bubbles) in the RH degasser to predict the circulation flow rate of water in a scaled down model and then the numerical solution has been extended to the real plant case for the prediction of steel circulation flow rate in the actual RH vessel. The prediction of the circulation flow rate of water from the present numerical solution matche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
49
0
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(54 citation statements)
references
References 17 publications
2
49
0
3
Order By: Relevance
“…In the Euler-Lagrange approach, liquid is treated as a continuum by solving the Navier-Stokes equations, whereas gas is solved by tracking a large number of bubbles through the calculated flow field. As demonstrated by Kishan,25 the predicted circulation rate with this approach for water modeling was considerably less than observation. Actually, the Euler-Lagrange approach requires that the gas-holdup is generally less than 12%.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…In the Euler-Lagrange approach, liquid is treated as a continuum by solving the Navier-Stokes equations, whereas gas is solved by tracking a large number of bubbles through the calculated flow field. As demonstrated by Kishan,25 the predicted circulation rate with this approach for water modeling was considerably less than observation. Actually, the Euler-Lagrange approach requires that the gas-holdup is generally less than 12%.…”
Section: Introductionmentioning
confidence: 93%
“…More importantly, these empirical correlations were obtained experimentally under a single nozzle; 20-23 nevertheless, a big difference of the gas-holdup distribution and plume shape were observed between multiple nozzles and a single nozzle in the case of horizontal gas blowing. 24 To overcome the shortcomings with the homogeneous fluid model, multiphase models, i.e., EulerianLagrangian and Eulerian-Eulerian approaches, [25][26][27][28][29] were put forward. In the Euler-Lagrange approach, liquid is treated as a continuum by solving the Navier-Stokes equations, whereas gas is solved by tracking a large number of bubbles through the calculated flow field.…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al 7) built a decarburization model by adding the fluid flow in the vacuum vessel and ladle. The flow pattern of steel melt in the ladle was analyzed by the computation fluid dynamics (CFD) [6][7][8][9][10][11][12][13][14][15] and perfect mixing time 14,15) was also calculated by the time-change in a tracer concentration at a given point after a tracer injection.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10][11][12][13][14][15][16][17][18][19] Some researches showed that the circulation flow rate is mainly determined by the vacuum degree and the lifting gas flow rate, [8][9][10][11][12] and it is difficult to increase the circulation flow rate after reaching its saturation value. 8,9) Meanwhile, several measures have also been taken to increase the circulation flow rate and shorten mixing time, such as increasing the diameter of the up snorkel and the down snorkel, 13) using the oval-shape-snorkels, 10) replacing one up snorkel and one down snorkel by three up snorkels and one down snorkel, 14) two up snorkels and one down snorkel or one up snorkel and two down snorkels, 12) applying rotating magnetic field around the up snorkel, 15) blowing additional argon gas, (e.g. blowing argon gas through vacuum chamber bottom 16) and ladle bottom 17,18) ) and so on.…”
Section: Introductionmentioning
confidence: 99%